2019
DOI: 10.1111/odi.13152
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of dry mouth following intraductal irrigation of salivary glands

Abstract: Objectives To assess the effect of major salivary gland intraductal irrigations (IGs) to relieve mouth dryness. Methods We retrospectively analyzed the records of patients with mouth dryness who underwent major salivary gland IG during 2013–2015. Records included demographics, medical background, dry mouth etiologies and symptomatology, and results of sialometry and sialo‐cone‐beam computerized tomography. Subjective improvement following the IG procedure (yes/no) and sustained subjective improvement (mouth dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Furthermore, the analysis of between-subject effects on UWSF measurements in their study showed statistically significant results for the use of a salivary gland manipulator as a negative prognostic factor, which corresponded to our previously published study [18] which identified anti-xerostomic medicine as a significant indicator for irresponsiveness to the irrigation treatment. Another study from the same institute [17] also demonstrated similar findings, and identified that different diagnosis/etiologies for dry mouth had no significant associations with subjective or objective improvements after irrigation therapies, which was similar to our results. Douglas et al [26] reported 88.1% of symptomatic resolution in a total of 59 patients with a history of either Sjogren's syndrome or post radioactive iodine therapy status after a corticosteroid injection and a ductal dilation in sialendoscopic surgery, and again disclosed no significant predictors of the ultimate success rates of sialendoscopy in these patient populations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the analysis of between-subject effects on UWSF measurements in their study showed statistically significant results for the use of a salivary gland manipulator as a negative prognostic factor, which corresponded to our previously published study [18] which identified anti-xerostomic medicine as a significant indicator for irresponsiveness to the irrigation treatment. Another study from the same institute [17] also demonstrated similar findings, and identified that different diagnosis/etiologies for dry mouth had no significant associations with subjective or objective improvements after irrigation therapies, which was similar to our results. Douglas et al [26] reported 88.1% of symptomatic resolution in a total of 59 patients with a history of either Sjogren's syndrome or post radioactive iodine therapy status after a corticosteroid injection and a ductal dilation in sialendoscopic surgery, and again disclosed no significant predictors of the ultimate success rates of sialendoscopy in these patient populations.…”
Section: Discussionsupporting
confidence: 91%
“…Salivary gland ductal irrigation is a therapeutic procedure involving the flushing of the salivary ducts with a variety of solutions to address conditions such as obstructive sialadenitis, chronic recurrent parotitis, and xerostomia. Saline solution, frequently utilized for its safety and non-irritating nature, mechanically removes debris [10,11,17]. Antibiotics like gentamicin [23] are directed towards bacterial pathogens, particularly in cases of sialadenitis or post-operative infections, although their inappropriate use can result in resistance and allergic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that exposure of salivary glands to stress results in the propagation of salivary gland stem cell capabilities due to cellular plasticity in the glands’ parenchyma. This could promote salivary gland repair [ 16 , 17 ]. Future (animal) studies should explore the effect of sialendoscopy on the ductal and acinar compartments to reveal the mechanism that accounts for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…This improved technology rekindled an interest in salivary imaging, including use of sialography, to assist in decision‐making regarding the role for sialendoscopy 4,5 . In addition, the intraductal irrigation done with bactericidal iodinated contrast in the course of performing a sialogram has helped with symptom control in selected cases 6–9 …”
Section: Introductionmentioning
confidence: 99%